VD_FINDINFO Décision / 2013 / 495 vom 8. Mai 2013 - VD Tribunal cantonal (2013)
DÉCISION D'IRRECEVABILITÉ, TIERS, DIFFAMATION, CALOMNIE, DEVOIR PROFESSIONNEL | 173 CP, 174 CP, 310 CPP (CH), 393 al. 1 let. a CPP (CH)